Hepatitis E Virus Genotype 3 in Colombia: Survey in Patients with Clinical Diagnosis of Viral Hepatitis (2016)
ABSTRACT: Background: Hepatitis E virus is a major cause of outbreaks as well as sporadic hepatitis cases worldwide. The epidemiology of this enterically transmitted infection differs between developing and developed countries. The aims of this study were to describe HEV infection in Colombian patients and to characterize the genotype. Methods: A prospective study was carried out on 40 patients aged over 15 with a clinical diagnosis of viral hepatitis, recruited from five primary health units in the city of Medellin, Colombia. Fecal samples obtained from the 40 consecutives cases were analyzed for HEV RNA using nested reverse transcription PCR for both ORF1 and ORF2-3. The amplicons were sequenced for phylogenetic analyses. Results: Nine (22.5%) cases of HEV infection were identified in the study population. Three HEV strains obtained from patients were classified as genotype 3. No significant association was found between cases of Hepatitis E and the variables water drinking source, garbage collection system and contact with pigs. Conclusions: This is the first prospective study of hepatitis E in Colombian patients. The circulation of the genotype 3 in this population is predictable considering the reports of the region and the identification of this genotype from pigs in the state of Antioquia, of which Medellin is the capital. Further studies are necessary to establish whether zoonotic transmission of HEV is important in Colombia.